1977
DOI: 10.1111/j.1751-1097.1977.tb09174.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultraviolet Light on Arrested Human Diploid Cell Populations

Abstract: The results of experiments to determine an effect of UV (254 nm) on human diploid fibroblasts (HDF) arrested with respect to division by using 0.5% fetal calf serum in the culture medium are reported. A fraction of cells from irradiated arrested populations, maintained in the arrested state post-irradiation, is lost from the populations. The extent of cell loss is hence-dependent and cell strain specific. A Xeroderma pigmentosum cell strain is more sensitive to UV than are normal HDF. No differences in sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…For comparison, we included an analysis of proliferating and quiescent 1BR.3. In complete medium, 1BR.3 proliferate rapidly but, when maintained under low serum conditions for 7 days, these cells enter stationary phase and arrest in G1 (Kantor et al, 1977). Figure 5 shows the abundance of each mRNA using isoform-specific primers for qPCR.…”
Section: Characterization Of Fancd2 Expression In Sh-sy5ymentioning
confidence: 99%
“…For comparison, we included an analysis of proliferating and quiescent 1BR.3. In complete medium, 1BR.3 proliferate rapidly but, when maintained under low serum conditions for 7 days, these cells enter stationary phase and arrest in G1 (Kantor et al, 1977). Figure 5 shows the abundance of each mRNA using isoform-specific primers for qPCR.…”
Section: Characterization Of Fancd2 Expression In Sh-sy5ymentioning
confidence: 99%
“…Nondividing (arrested) populations of human fibroblasts were established and maintained by a modification of established procedures (18,19). Freshly trypsinized fibroblasts were plated into a series of 6-cm (diameter) tissue culture dishes at a cell density of 1.6 x 105 cells per dish and were incubated for 24 hr in medium supplemented with 15% serum.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that diploid human cells that have been arrested by reducing the serum concentration to 0.5% have normal levels of UDS (8). Incubation of various XP cell lines in 0.5% serum for a minimum of 14 days usually reduces the amount of replication synthesis during a 2-hr labeling period to <0.1%.…”
Section: Resultsmentioning
confidence: 99%